The effect of corporate governance on the cost of debt capital - Eskandari, Alireza (2016)
Agency theory predicts that corporate governance (CG) and audit quality (AQ) enhance the convergence of interests between shareholders and managers and enable investors and lenders to have better perception on the optimum level of cost of debt capital. However, there is a lack of studies that investigate this issue in the emerging markets, particularly in Malaysia. Therefore, this research is conducted to investigate the relationship between internal monitoring characteristics of board of director and audit committee relating to the size, independence, financial expertise, frequency of meeting, ethnicity and education of directors and ethnicity of chairperson, and AQ as proxies by audit fees, non-audit service fees and industry specialist auditor, as external monitoring on the cost of debt capital. This study reports the results of multivariate analysis on dataset that were obtained from the Bursa Malaysia, DataStream, Bloomberg and annual reports of firms between 2003 and 2012. The empirical results of this study indicate that larger size and independent nonexecutive directors with less frequent directors’ meeting, ethnicity of Malay directors on the board, larger size and more frequent meeting of audit committee have significant effects on reducing the agency problem with internal monitoring function. These lead to a reduction in the cost of raising fund from lenders in capital market. The results also indicate that hiring industry specialist auditors and using non-audit services of external auditors have remarkable influence on reducing the information asymmetry with external monitoring function, which help to lower the cost of debt capital in the capital market. Findings are consistent with the agency theory, signaling theory and cultural theory, whereby internal and external CG mechanisms are associated with effective monitoring, which in turn helps to lower information asymmetry and agency problem in capital markets and consequently increases potential investors and lenders. The findings are of potential interest to policy makers, board members, audit committee members and external auditors.